Investigation and modelling of ultra-fast processes of energy transport : super-transport of energy - Yulia Levinskaya (2013)
This work is devoted to an investigation of ultra-fast processes of energy transport. There is a close link between ultra-fast and nano-scale processes. However, modern science lacks understanding of energy transport phenomena, which occurs at nano- space and time scales. In fact, a realistic model of such processes does not exist. It was recently found that the phase-lagging models used to model ultra-fast processes lead to the existence of superfluid regime without low temperature condition. Still, the existing models are phenomenological and the kinetic theory cannot be used to describe these processes in any medium due to its limitations. The research is focused on the existence of the fundamental time lag problem in the processes of heat transport. Quantum theory is a completely new approach in this area. It is used to solve the problem of the time lag existence and to estimate its value. It is proved in this thesis that the macroscopic equation for the second sound follows from the quantum equation for de Broglie’s wave packet. It was shown that the result is consistent with the outcomes obtained previously from different theories. The investigation of the behavior of the apparent thermal diffusivity and viscosity was conducted as well as a study of the steady state heat transfer within a nano-scale spatial domain and apparent sources. The experiment was conducted to validate the resulting mathematical model, which appears to be in good agreement with the data obtained.